Electron transport material, perovskite solar cell and electric device

CN119522228APending Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054262.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing perovskite solar cells, especially trans-structured devices, have low stability and efficiency. The use of fullerene-based materials leads to lower open circuit voltage, poor film morphology, and easy accumulation and adsorption of moisture and oxygen, resulting in poor performance. deterioration.

Method used

Provide an electron transport material whose structural features include repeating structural units and electron-withdrawing end groups. It is prepared through free radical polymerization. The HOMO-LUMO energy level of the material is adjusted to be close to that of perovskite materials, thereby improving the electron transport characteristics and stability. Perovskite/ETL interface reduces water penetration and ion migration.

Benefits of technology

Significantly improves the stability and efficiency of perovskite solar cells. Compared with fullerene-based materials, it is more stable, forms a dense film, effectively protects the perovskite active layer, reduces the contact between perovskite and oxygen, and improves the overall device quality. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522228A_ABST
    Figure CN119522228A_ABST
Patent Text Reader

Abstract

The invention relates to an electron transport material, a perovskite solar cell and an electric device. The electron transport material has the structural characteristics shown in the following formula (I). According to the electron transport material, A0 is used as a main body framework, the molecular structure of the material is regulated and controlled in cooperation with end groups B1 and B2 of a specific structure, receptor units are matched with one another, the stability of a perovskite solar cell, especially a trans-structure perovskite solar cell can be effectively improved, meanwhile, the electron transport material has good electron transport characteristics, and the electron transport efficiency is improved. And the efficiency of the perovskite solar cell is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Electron transport materials, perovskite solar cells and electrical devices Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to an electron transport material, a perovskite solar cell and an electrical device. Background Art

[0002] Perovskite solar cells have attracted increasing attention in recent years due to their excellent optoelectronic properties and rapidly improving power conversion efficiency (PCE). Planar devices with a stacked electron transport layer (ETL), perovskite layer, and hole transport layer (HTL) are gaining attention as they exhibit high efficiency and have a simpler device structure, making them more attractive for large-scale production.

[0003] Currently, planar devices can have either a formal or trans structure, and the stability of both formal and trans structures of perovskite solar cells needs to be further improved.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide an electron transport material that can be applied to perovskite solar cells and improve their efficiency and stability.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides an electron transport material having the structural characteristics shown in the following formula (I):

[0007] Wherein, A0 represents a repeating structural unit, the repeating structural unit includes one or more of a substituted or unsubstituted aryl ring system and a substituted or unsubstituted heteroaryl ring system, and the repeating structural unit is an electron-withdrawing group;

[0008] B1 and B2 represent end groups, each of which is an electron-withdrawing group, and each independently contains one or more of O, S, F, Cl, Br and I;

[0009] n represents the number of repeating structural units.

[0010] The above-mentioned electron transport material uses A0 as the main skeleton and cooperates with the end groups B1 and B2 of specific structures to regulate the molecular structure of the material. The receptor units cooperate with each other, which can effectively improve the stability of perovskite solar cells, especially inverted structure perovskite solar cells. At the same time, it has good electron transport properties and improves the efficiency of perovskite solar cells.

[0011] In one embodiment, B1 and B2 are each independently cyanoacetic acid and its derivatives, 1,3-dimethyl-2,4,6-trioxohexahydropyrimidine and its derivatives, oxothioketothiazolidine and its derivatives, indene dione and its derivatives, or thiophene indenone and its derivatives. For different repeating structural units, the types of B1 and B2 can be appropriately selected to adjust the HOMO-LUMO energy levels of the material molecules to the band gap of the perovskite of different components, bringing them closer together, thereby improving the open circuit voltage and battery efficiency.

[0012] Furthermore, B1 and B2 are each independently one of the following groups:

[0013] wherein R1 is each independently H, C1-C18 alkyl, or halogen-substituted C1-C18 alkyl;

[0014] R2 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl.

[0015] In one embodiment, the monomers forming A0 include one or more of benzotriazole (BTA) and its derivatives, benzothiadiazole (BT) and its derivatives, benzoselenadiazole (BS) and its derivatives, thienothiophene (TT) and its derivatives, thienopyrroledione (TPD) and its derivatives, benzodithiophenedione (BDD) and its derivatives, quinoxaline (Qx) and its derivatives, naphthalene diimide (NDI) and its derivatives, perylenetetracarboxylic diimide (PDI) and its derivatives, and bithiophene imide (BTI) and its derivatives. By using different A0s in combination with B1 and B2, the energy level of the material can be controlled.

[0016] Furthermore, A0 is independently one of the following groups:

[0017] wherein R3 are each independently H, C1-C18 alkyl or halogen-substituted C1-C18 alkyl;

[0018] R4 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl.

[0019] In one embodiment, n=2-32; optionally, n is a multiple of 2; optionally, n is 2-16.

[0020] In one embodiment, the electron transport material has a HOMO energy level of -7.14 eV to -6.47 eV and a LUMO energy level of -3.83 eV to -3.32 eV. The HOMO and LUMO energy levels of the electron transport material are close to those of the perovskite material, which facilitates electron migration and improves open circuit voltage and battery efficiency.

[0021] The second aspect of the present application also provides a method for preparing the electron transport material according to the first aspect, comprising the following steps:

[0022] Compound 1 and compound 2 are subjected to a free radical polymerization reaction;

[0023] Among them, the structural formula of compound 1 is The structural formula of compound 2 is

[0024] A0, B1, and B2 have the same meanings as in claim 1, and n1+n2=n.

[0025] The preparation method has simple steps, the reaction process is easy to control, and is convenient for large-scale application.

[0026] In one embodiment, the free radical polymerization reaction conditions include: reacting in the presence of a halogenated reagent and under light conditions. The free radical polymerization reaction is initiated by light, and the steps are simple and easy to control.

[0027] Furthermore, the halogenating agent is N-bromosuccinimide.

[0028] Furthermore, the solvent used in the reaction includes an alkane solvent.

[0029] Furthermore, the reaction time is 2 min to 10 min.

[0030] Furthermore, the illumination is performed using a mercury lamp, and the power of the mercury lamp is 400W to 600W.

[0031] In one embodiment, the preparation steps of compound 1 include:

[0032] Substitution reaction of compound 1-1 with compound 1-2;

[0033] Among them, the structural formula of compound 1-1 is B1——B(OH)2, and the structural formula of compound 1-2 is X2 is halogen.

[0034] In one embodiment, the preparation steps of compound 3 include:

[0035] Substitution reaction of compound 3-1 with compound 3-2;

[0036] Among them, the structural formula of compound 3-1 is B2——B(OH)2, and the structural formula of compound 3-2 is X3 is halogen.

[0037] In one embodiment, the conditions of the substitution reaction include: performing the reaction in the presence of a catalyst.

[0038] Furthermore, the catalyst includes tetrakis(triphenyl)phosphine palladium.

[0039] Furthermore, the reaction temperature is heated to reflux, and the reaction time is 10 h to 30 h.

[0040] Furthermore, the solvent used in the reaction includes one or both of tetrahydrofuran and water.

[0041] The third aspect of the present application further provides a perovskite solar cell, comprising the electron transport material described in the first aspect of the present application. The perovskite solar cell has good stability and high efficiency.

[0042] The fourth aspect of the present application provides an electrical device, comprising the electron transport material of the first aspect of the present application or the perovskite solar cell of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] FIG1 is a schematic structural diagram of a perovskite solar cell according to an embodiment of the present application;

[0044] FIG2 is a schematic diagram of an electrical device using a perovskite solar cell as a power source according to an embodiment of the present application. DETAILED DESCRIPTION

[0045] Below, the embodiments of the electron transport material, perovskite solar cell, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0046] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0051] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0052] If not otherwise specified, in this application, "substituted" means that it can be substituted by conventional groups in the art, for example, one or more of H, alkyl, halogen, halogen-substituted alkyl, etc.

[0053] Research has shown that in the structural design of inverted perovskite solar cells, the electron transport layer (ETL), as the topmost layer and closest to the environment, significantly influences the device's performance and stability. Furthermore, defects in the perovskite layer (typically lattice vacancies, interstitials, or insufficiently coordinated ions) are primarily located on the film surface and grain boundaries, closely contacting the ETL. Therefore, rationally designing the ETL material for perovskite solar cells, particularly inverted perovskite solar cells, is one of the keys to improving their efficiency and stability.

[0054] Currently, fullerene-based materials are the most common ETLs in perovskite solar cells. Studies have found that they have several drawbacks that can lead to reduced efficiency and stability in perovskite solar cells using fullerene-based ETLs: First, the widespread distribution of band tail states in fullerene-based materials leads to a decrease in open-circuit voltage (Voc), thereby reducing efficiency. Second, the thickness of fullerene materials is limited by the conductivity of the layer and their low solubility in solution processing, resulting in poor film morphology and the potential for direct contact between the perovskite and the electrode. For example, the commonly used fullerene derivative ETL, [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), has poor adhesion to the perovskite layer, resulting in aggregation of morphologically modified molecules, which in turn reduces device stability. Third, fullerene materials adsorb moisture and oxygen, resulting in an increased dipole moment and resistance, which in turn degrades device performance. Finally, studies have shown that even without exposure to oxygen and moisture, devices using PCBM as an ETL rapidly degrade under light, failing to provide an adequate barrier to the migration of perovskite layer decomposition products and their reaction with the metal electrode. At the same time, compared with regular structure perovskite solar cells, the problem is particularly prominent in inverted structure perovskite solar cells.

[0055] Based on this, an example of the present application provides an electron transport material having the structural characteristics shown in the following formula (I):

[0056] Wherein, A0 represents a repeating structural unit, the repeating structural unit includes one or more of a substituted or unsubstituted aryl ring system and a substituted or unsubstituted heteroaryl ring system, and the repeating structural unit is an electron-withdrawing group;

[0057] B1 and B2 represent end groups, each of which is an electron-withdrawing group, and each independently contains one or more of O, S, F, Cl, Br and I;

[0058] n represents the number of repeating structural units.

[0059] The above-mentioned electron transport material uses A0 as the main skeleton and cooperates with the end groups B1 and B2 of specific structures to regulate the molecular structure of the material. The receptor units cooperate with each other, which can effectively improve the stability of perovskite solar cells, especially inverted structure perovskite solar cells. At the same time, it has good electron transport properties and improves the efficiency of perovskite solar cells.

[0060] Furthermore, these electron transport materials, through their appropriate end-group structures, can improve the perovskite / ETL interface, reducing water penetration and ion migration, thereby further enhancing the efficiency and stability of perovskite solar cells. Furthermore, compared to fullerene-based materials, these electron transport materials are more stable to sunlight, heat, and oxygen, forming denser films. This allows them to more effectively protect the perovskite active layer, reduce perovskite contact with oxygen, and improve device stability.

[0061] In some examples, the electron transport material is an n-type polymer.

[0062] In some examples, B1 and B2 are each independently cyanoacetic acid and its derivatives, 1,3-dimethyl-2,4,6-trioxohexahydropyrimidine and its derivatives, oxothioketothiazolidine and its derivatives, indene dione and its derivatives, or thiophene indenone and its derivatives. For different repeating structural units, the types of B1 and B2 can be reasonably selected to adjust the HOMO-LUMO energy levels of the material molecules to the band gaps of the perovskites of different components, bringing them closer together, thereby improving the open circuit voltage and battery efficiency.

[0063] In some examples, B1 and B2 are each independently one of the following groups:

[0064] wherein R1 is each independently H, C1-C18 alkyl or halogen-substituted C1-C18 alkyl, and further, R1 is each independently H;

[0065] R2 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl. Further, R2 is each independently H.

[0066] In some examples, B1 and B2 are the same group, which can simplify the material preparation process.

[0067] In some examples, the monomers forming A0 include one or more of benzotriazole (BTA) and its derivatives, benzothiadiazole (BT) and its derivatives, benzoselenadiazole (BS) and its derivatives, thienothiophene (TT) and its derivatives, thienopyrroledione (TPD) and its derivatives, benzodithiophenedione (BDD) and its derivatives, quinoxaline (Qx) and its derivatives, naphthalene diimide (NDI) and its derivatives, perylenetetracarboxylic diimide (PDI) and its derivatives, and bithiophene imide (BTI) and its derivatives.

[0068] It is understandable that the types of n monomers can be the same or different. By combining different monomers, materials with different performance advantages can be achieved, without limitation. For example, the use of BTA, BT, BS or their derivatives can reduce the Urbach band tail (energy) to reduce non-radiative recombination, and the increase in filling factor can be used to construct low-bandgap polymers, and is beneficial to carrier transport, thereby facilitating the improvement of the short-circuit current of the device; the use of TT or its derivatives can enhance the stability of the compound structure, making it easier for carriers to be transported between molecules; the use of TPD, BDD, Qx, NDI, PDI or their derivatives can optimize the morphology and / or charge transport capacity of the material; the use of BTI or its derivatives can enhance the hydrophobicity of the material, and have good film-forming properties, which is beneficial to improving the isolation from water and oxygen, while also passivating the defects of the perovskite interface, improving the carrier transport capacity, and thereby improving the battery efficiency.

[0069] In some examples, A0 is each independently one of the following groups:

[0070] wherein R3 is each independently H, C1-C18 alkyl or halogen-substituted C1-C18 alkyl, and further, R3 is each independently H;

[0071] R4 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl. Further, R4 is each independently H.

[0072] In some examples, each A0 is the same group, which can simplify the material preparation process.

[0073] In some examples, the derivative groups (or R1-R4) involved in A0, B1, and B2 are halogenated groups. Halogenation (fluorine, chlorine, bromine, etc.) on the end groups B1 and B2 can expand absorption, lower energy levels, and increase intra- and intermolecular interactions, thereby effectively controlling the photoelectrochemical properties, crystallinity, and π-π stacking of the molecules, thereby rationally controlling the morphology and charge transport of the material, improving stability and efficiency. It can also specifically passivate the X vacancies at the perovskite grain boundaries, further increasing their stability, and can inhibit non-radiative recombination in the battery, improving device efficiency.

[0074] In some examples, the derivative groups include alkane chains of varying lengths, halogenated alkane chains of varying lengths, and their isomeric groups. This allows for solubility and morphology control, thereby facilitating material preparation and film formation, resulting in larger crystal units, improved fill factors, and improved carrier transport.

[0075] In addition, by using different derivative groups (or R1 to R4) involved in A0, B1 and B2, it is also possible to adjust the energy level of the material.

[0076] In some examples, n=2 to 32. Further, n is a multiple of 2. Without limitation, the value of n includes, but is not limited to, 2, 4, 8, 10, 12, 16, 20, 24, 26, 28, 30, and 32.

[0077] In some examples, the electron transport material has a HOMO energy level of 6.53 eV to 7.14 eV and a LUMO energy level of 3.32 eV to 3.83 eV. The HOMO and LUMO energy levels of the electron transport material are close to those of the perovskite material, which facilitates electron migration and improves open circuit voltage and battery efficiency.

[0078] Another example of the present application also provides a method for preparing the electron transport material as described above, comprising the following steps:

[0079] Compound 1 and compound 2 are subjected to a free radical polymerization reaction;

[0080] Among them, the structural formula of compound 1 is The structural formula of compound 2 is

[0081] A0, B1, and B2 have the same meanings as in claim 1, and n1+n2=n.

[0082] The preparation method has simple steps, the reaction process is easy to control, and is convenient for large-scale application.

[0083] In some examples, the free radical polymerization reaction conditions include: reacting in the presence of a halogenated reagent and under light conditions. The free radical polymerization reaction is initiated by light, and the steps are simple and easy to control.

[0084] Furthermore, the halogenating agent is N-bromosuccinimide (NBS).

[0085] Furthermore, the solvent used in the reaction includes an alkane solvent. Without limitation, the alkane solvent is hexane.

[0086] Furthermore, the reaction time is 2 min to 10 min.

[0087] Furthermore, the illumination is performed using a mercury lamp, and the power of the mercury lamp is 400W to 600W.

[0088] In addition, in some examples, the preparation steps of Compound 1 include:

[0089] Substitution reaction of compound 1-1 with compound 1-2;

[0090] Among them, the structural formula of compound 1-1 is B1——B(OH)2, and the structural formula of compound 1-2 is X2 is halogen.

[0091] In addition, in some examples, the preparation steps of compound 3 include:

[0092] Substitution reaction of compound 3-1 with compound 3-2;

[0093] Among them, the structural formula of compound 3-1 is B2——B(OH)2, and the structural formula of compound 3-2 is X3 is halogen.

[0094] Furthermore, in the process of preparing compound 1 and / or compound 3, the conditions of the substitution reaction include: performing the reaction in the presence of a catalyst. Furthermore, the substitution reaction is performed in the presence of an alkaline reagent. Without limitation, the alkaline reagent can be provided as a carbonate.

[0095] Furthermore, the catalyst includes tetrakis(triphenyl)phosphine palladium.

[0096] Furthermore, the reaction temperature is heated to reflux, and the reaction time is 10 hours to 30 hours. It can be understood that the temperature of heating to reflux can be determined according to the type of solvent. For example, in a mixed solvent of tetrahydrofuran and water, the heating temperature can be 80°C to 90°C.

[0097] Furthermore, the solvent used in the reaction includes one or both of tetrahydrofuran (THF) and water.

[0098] In some examples of the present application, a perovskite solar cell is provided, comprising a transparent electrode, a functional layer and an electrode layer sequentially stacked on the transparent electrode, the functional layer comprising an electron transport layer, a hole transport layer, and a perovskite layer disposed between the electron transport layer and the hole transport layer; the electron transport layer comprises the electron transport material described above. The perovskite solar cell has good stability and high efficiency.

[0099] As an example, the perovskite solar cell 100 includes the structure shown in FIG1 , which includes a substrate layer 110, a first electrode 120, a first transport layer 130 (electron transport layer or hole transport layer), a perovskite layer 140, a second transport layer 150 (hole transport layer or electron transport layer), and a second electrode 160. Furthermore, the structural layers are stacked in sequence as shown in the figure.

[0100] In some examples, the hole transport layer is closer to the transparent electrode than the electron transport layer.

[0101] Without limitation, the electron transport layer can be prepared by directly dissolving the material of the electron transport layer in an organic solvent, forming a film by spin coating, spray coating, blade coating, or slit coating, and then removing the organic solvent by annealing or vacuum. Specifically, the organic solvent can be one or more of toluene, chlorobenzene, and dichloromethane, and the concentration of the electron transport layer material therein can be 20 to 100 mg / mL.

[0102] In some examples, the thickness of the electron transport layer is 5 nm to 100 nm.

[0103] It can be understood that perovskite solar cells include both regular and inverted structures. For the regular structure, a perovskite solar cell includes a transparent electrode and an electron transport layer, a perovskite layer, a hole transport layer, and an electrode layer stacked in sequence on the transparent electrode. For the inverted structure, the perovskite solar cell includes a transparent electrode and a hole transport layer, a perovskite layer, an electron transport layer, and an electrode layer stacked in sequence on the transparent electrode.

[0104] Specifically, the material of the perovskite layer can be any conventional material in the art. Without limitation, the general structural formula of the perovskite layer material is ABX3 or A2CDX6, where A is a monovalent cation, B is a divalent metal cation, C and D are a monovalent metal cation and a trivalent metal cation, respectively, and X is a monovalent anion.

[0105] Without limitation, the A includes organic cations, Li + 、Na + , K + , Rb +and Cs + One or more of; Optionally, the organic cation includes methylamine (MA + ), ethylamino, propylamino, butylamino, pentylamino, hexylamino, formamidinium (FA + ) and at least one of imidazole; Optionally, the A comprises an organic amine ion and Cs + One or more of .

[0106] Without limitation, the B includes Pb 2+ 、Sn 2+ 、Be 2+ Mg 2+ , Ca 2+ 、Sr 2+ 、Ba 2+ 、Zn 2+ 、Ge 2+ 、Fe 2+ 、Mn 2+ 、Co 2+ 、Sb 2+ 、Cu 2+ and Ni 2+ One or more of; Optionally, B includes Pb 2+ and Sn 2+ One or both of .

[0107] Without limitation, the C includes Ag + 、Cs + , K + and Ru + One or more of.

[0108] Without limitation, the D includes Bi 3+ 、N i3+ 、Fe 3+ 、Cu 3+ 、Sb 3+ and In 3+ One or more of .

[0109] Without limitation, the X includes I - Br - and Cl - One or more of .

[0110] In some examples, the band gap of the perovskite layer is 1.20 eV to 2.30 eV. The band gap can be measured by ultraviolet absorption spectroscopy to obtain an ultraviolet absorption curve, and then calculated using the Tauc equation to obtain the band gap.

[0111] In some examples, the thickness of the perovskite layer is 200 nm to 1000 nm.

[0112] Without limitation, the transparent electrode is a transparent conductive glass substrate, and materials thereof include FTO, ITO, AZO, BZO, IZO, and the like.

[0113] Without limitation, the hole transport layer can be at least one of the following materials and their derivatives and materials obtained by doping or passivation thereof: nickel oxide, 2,2',7,7'-tetrakis(N,N-p-methoxyanilino)-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphate (Me-4Pacz), poly[bis(4-phenyl)(2 ,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), triphenylamine with triptycene as the core (H101), 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), N-(4-phenylamino)carbazole-spirobifluorene (CzPAF-SBF), poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), polythiophene, molybdenum oxide (MoO3), cuprous iodide (CuI), cuprous oxide (CuO), etc.

[0114] Without limitation, the material of the electrode layer may be an organic, inorganic, or organic-inorganic hybrid conductive material, for example, Ag, Cu, C, Au, Al, ITO, AZO, BZO, IZO, etc.

[0115] Specifically, the perovskite solar cell is formal, and its preparation method includes the following steps:

[0116] Step 1: Etch and clean the transparent electrode and dry it;

[0117] Step 2: preparing an electron transport layer on the transparent electrode;

[0118] Step 3: Preparing a perovskite layer on the electron transport layer;

[0119] Step 4: preparing a hole transport layer on the perovskite layer; specifically, preparing a hole transport solution and placing it on the surface of the perovskite layer, and then removing the solvent by annealing or vacuuming;

[0120] Step 5: preparing an electrode layer on the hole transport layer; optionally, also including the step of performing an edge clearing test.

[0121] Specifically, the perovskite solar cell is in the trans type, and its preparation method comprises the following steps:

[0122] Step 1: Etch and clean the transparent electrode and dry it;

[0123] Step 2: preparing a hole transport layer on the transparent electrode; specifically, preparing a hole transport solution and placing it on the surface of the transparent electrode, and then removing the solvent by annealing or vacuuming;

[0124] Step 3: Preparing a perovskite layer on the hole transport layer;

[0125] Step 4: preparing an electron transport layer on the perovskite layer;

[0126] Step 5: preparing an electrode layer on the electron transport layer; optionally, also including the step of performing an edge clearing test.

[0127] The present application provides an electrical device, comprising at least one of the above-mentioned perovskite solar cell and the perovskite solar cell prepared by the above-mentioned solar cell preparation method.

[0128] In some examples, the solar cell can be used as a power source for an electrical device or as an energy storage unit for an electrical device.

[0129] Furthermore, the above-mentioned electrical devices may include mobile devices, such as mobile phones, laptop computers, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0130] FIG2 shows an example of an electric device, which may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0131] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc.

[0132] Example

[0133] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0134] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.

[0135] 1. Preparation Example

[0136] Preparation Example 1

[0137] The synthesis method of the electron transport layer material 1 is as follows:

[0138] Under an inert atmosphere, a mixture of compound 1 (1.2 g, 3.2 mmol), bis(tributyltin) (2.5 g, 4.3 mmol), Pd(PPh 3 ) 4 (180 mg, 0.16 mmol) in 10 ml of anhydrous toluene and 10 ml of DMF was stirred at 100° C. for 24 hours. After completion of the reaction, the mixture was quenched with 10 ml of H 2 O. The mixture was then extracted three times with DCM and the organic phases were combined. The combined organic phases were washed with water (2×20 ml) and dried over MgSO 4 . The solvent was evaporated and the residue was purified with silica gel (DCM / n-hexane=3 / 2 volume ratio) to give solid compound 2 (0.84 g, 89%).

[0139] Compound 2 (472 mg, 0.8 mmol) was dissolved in 25 ml of DMF, and NBS (142 mg, 0.8 mmol) dissolved in 15 ml of DMF was added dropwise to the solution at 0°C for 1.5 hours. The reaction mixture was stirred in the dark for 2 hours at 0°C. The mixture was then poured into water and extracted with dichloromethane. The organic phase was dried over anhydrous MgSO4, and the solvent was then evaporated under vacuum. The crude product was purified on silica gel chromatography using a DCM / hexane mixture (3 / 2 volume ratio) as eluent to separate solid compound 3 (365 mg, 68%).

[0140] Under inert atmosphere, compound 3 (200 mg, 0.3 mol), compound 4 (200 mg, 0.6 mmol), Pd (PPh 3 ) 4 (70 mg, 0.06 mmol) and sodium carbonate (159 g, 1.5 mmol) are dispersed in 15 ml of THF and 1.5 ml of H in a mixed solvent of O. The resulting mixture is stirred at 85°C for 24 hours. The reaction is cooled to room temperature, extracted with DCM for 3 times, and the organic phase is combined. The combined organic fractions are washed with water (3 × 20 ml) and dried over MgSO 4 . The solvent is evaporated under vacuum and purified by silica gel chromatography (DCM / hexane=1 / 1 volume ratio) to obtain compound 5 (203 mg, 85%).

[0141] Compound 5 (50 mg, 0.06 mmol) was dissolved in 5 ml of hexane, and NBS (33 mg, 0.19 mmol) was added to the solution. The solution was sealed in a glass bottle with N2 protection. The reaction was then stirred under a 500W mercury lamp for 3 minutes. The reaction solvent was evaporated under vacuum, and the resulting residue was further purified by silica gel chromatography using DCM as an eluent to obtain the target product 6 (i.e., electron transport layer material 1) (35 mg, 70%) as a solid.

[0142] NMR spectrum data of electron transport layer material 1:

[0143] 1 H NMR (400MHz, CDCl3): 8.04 (4H,s), 8.61 (2H,s), 12.56 (2H,s), 13.40 (4H,s).

[0144] The synthesis methods of Preparation Examples 2-14 and Preparation Comparative Example 3 are similar to Preparation Example 1, but the types of A0, B1 (B2) and the value of n are changed, see Table 1 for details.

[0145] Table 1

[0146] NMR spectrum data of electron transport layer material 2:

[0147] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.01(1H,s), 7.93(1H,s), 3.22(12H,s).

[0148] NMR spectrum data of electron transport layer material 3:

[0149] 1 H NMR (400MHz, CDCl3): 13.4(1H,s),8.04(1H,s),7.44(2H,s),5.62(2H,s),4.67(4H,s),5.11(4H,q),1.20(2H,t).

[0150] NMR spectrum data of electron transport layer material 4:

[0151] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.04(1H,s), 8.46(2H,s), 7.93(4H,d), 7.71(4H,d).

[0152] NMR spectrum data of electron transport layer material 5:

[0153] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.04(1H,s), 8.48(2H,s), 7.70(2H,s), 7.39(2H,s).

[0154] NMR spectrum data of electron transport layer material 6:

[0155] 1 H NMR (400MHz, CDCl3): 12.56 (2H, s), 8.22 (1H, s), 7.95 (1H, s), 7.29 (2H, d).

[0156] NMR spectrum data of electron transport layer material 7:

[0157] 1 H NMR (400MHz, CDCl3): 13.31(1H,s), 12.56(2H,s), 8.61(1H,s), 7.70(1H,s).

[0158] NMR spectrum data of electron transport layer material 8:

[0159] 1 H NMR (400MHz, CDCl3): 12.56(2H,s),8.74(2H,s),8.22(1H,s),7.95(1H,s),7.67(2H,s).

[0160] NMR spectrum data of electron transport layer material 9:

[0161] 1 H NMR (400MHz, CDCl3): 12.56 (2H,s), 10.02 (1H,s), 8.61 (2H,s), 8.15 (2H,s).

[0162] NMR spectrum data of electron transport layer material 10:

[0163] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.01(1H,s), 7.93(1H,s), 3.22(12H,s).

[0164] NMR spectrum data of electron transport layer material 11:

[0165] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.01(1H,s), 7.93(1H,s), 3.22(12H,s).

[0166] NMR spectrum data of electron transport layer material 12:

[0167] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.01(1H,s), 7.93(1H,s), 3.22(12H,s).

[0168] NMR spectrum data of electron transport layer material 13:

[0169] 1 H NMR (400MHz, CDCl3): 7.90 (1H, s), 7.84 (2H, s), 4.32 (2H, t), 3.97 (4H, t), 1.78-0.88 (33H, m).

[0170] NMR spectrum data of electron transport layer material 14:

[0171] 1 H NMR (400MHz, CDCl3): 8.64 (2H, s), 4.32 (2H, t), 3.97 (4H, t), 1.78-0.88 (33H, m).

[0172] NMR spectrum data of electron transport layer material D:

[0173] 1 H NMR (400MHz, CDCl3): 13.4(1H,s), 8.04(1H,s), 3.83(6H,s).

[0174] 2. Application Examples

[0175] Example 1

[0176] 1) Take 20 pieces of 2.0*2.0cm FTO conductive glass and remove 0.35cm of FTO at each end by laser etching to expose the glass substrate;

[0177] 2) Ultrasonic cleaning of the etched FTO conductive glass with water, acetone, and isopropyl alcohol several times in sequence;

[0178] 3) The FTO conductive glass was blown dry with a nitrogen gun to remove the solvent and then placed in a UV ozone machine for further cleaning;

[0179] 4) NiOx was prepared on the FTO substrate after UV ozone treatment by magnetron sputtering, and annealed on a hot plate at 200°C for 20 minutes after preparation;

[0180] 5) Spin-coat a 2 mg / mL PTAA solution on the NiOx layer at 6000 rpm. After spin-coating, anneal at 100°C for 10 minutes and cool to room temperature.

[0181] 6) Weighing lead iodide, iodomethane, and cesium iodide, dissolving them in a mixed solution of DMF and DMSO, stirring for 2 h, and filtering through a 0.22 μm amphoteric filter to obtain a perovskite precursor solution; spin-coating the perovskite precursor solution on the PTAA layer at 4000 rpm, annealing at 100° C. for 10 minutes, and cooling to room temperature, wherein the active material of the perovskite absorber layer is a CsFA system;

[0182] 7) Weigh a certain amount of electron transport layer material 1 and dissolve it in chlorobenzene to obtain an electron transport layer solution. Spin-coat the hole transport layer solution on the perovskite absorption layer at 3000 rpm. After spin coating, anneal on a hot plate at 70°C for 5 minutes. Then, apply 60 μL of a BCP isopropanol solution of a certain concentration (e.g., 0.5 mg / mL) to the electron transport layer at 5000 rpm.

[0183] 8) The obtained wafer is placed in a vapor deposition machine, and a metal electrode Ag 100 nm is vapor deposited to obtain a perovskite solar cell 1.

[0184] The perovskite solar cells of Examples 2-14 and Comparative Examples 1-3 are prepared in a similar manner to Example 1, but use the electron transport layer materials of the corresponding Preparation Examples, and Comparative Example 1 uses PCBM as the electron transport layer material, Comparative Example 2 uses C60 as the electron transport layer material, and Comparative Example 3 uses the electron transport layer material of Preparation Comparative Example 3.

[0185] 3. Battery performance test

[0186] 1. Photoelectric conversion efficiency:

[0187] The test of perovskite solar cells (IV test) uses Guangyan's solar simulator, which complies with the national standard IEC61215 for testing. The light intensity is calibrated using crystalline silicon solar cells to reach the intensity of one sun, AM 1.5. The battery is connected to a digital source meter and its photoelectric conversion efficiency is measured under light.

[0188] 2. Stability:

[0189] According to the method of "1", the photoelectric conversion efficiency of the perovskite solar cell was tested under N2 atmosphere protection and RH85% for 3 days and 30 days respectively.

[0190] The test results are shown in Table 2 below.

[0191] Table 2

[0192] As shown in Table 2, compared with Comparative Examples 1-2 using traditional electron transport layer materials C60 and PCBM, Examples 1-14 have significantly improved stability while maintaining comparable battery efficiency to Comparative Examples 1-2. Furthermore, a comparison between Example 1 and Comparative Example 3 shows that the present application can improve battery efficiency and stability by adopting a suitable end group structure.

[0193] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electron transport material having the structural characteristics shown in the following formula (I): in, A0 represents a repeating structural unit, the repeating structural unit includes one or more of a substituted or unsubstituted aryl ring system and a substituted or unsubstituted heteroaryl ring system, and the repeating structural unit is an electron withdrawing group; B1 and B2 represent end groups, which are electron-withdrawing groups, and the structures of each independently contain one or more of O, S, F, Cl, Br and I; n represents the number of repeating structural units.

2. The electron transport material according to claim 1, characterized in that B1 and B2 are each independently cyanoacetic acid and its derivative groups, 1,3-dimethyl-2,4,6-trioxohexahydropyrimidine and its derivative groups, oxothioketothiazolidine and its derivative groups, indanedione and its derivative groups or thiopheneindanone and its derivative groups.

3. The electron transport material according to claim 1 or 2, characterized in that B1 and B2 are each independently one of the following groups: wherein R1 is independently H, C1-C18 alkyl or halogen-substituted C1-C18 alkyl; R2 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl.

4. The electron transport material according to any one of claims 1 to 3, characterized in that The monomers forming A0 include one or more of benzotriazole and its derivatives, benzothiadiazole and its derivatives, benzoselenadiazole and its derivatives, thienothiophene and its derivatives, thienopyrroledione and its derivatives, benzodithiophenedione and its derivatives, quinoxaline and its derivatives, naphthalene diimide and its derivatives, perylenetetracarboxylic acid diimide and its derivatives, and bithiophene imide and its derivatives.

5. The electron transport material according to any one of claims 1 to 4, characterized in that A0 is independently one of the following groups: wherein R3 is each independently H, C1-C18 alkyl or halogen-substituted C1-C18 alkyl; R4 is each independently H, F, Cl, Br, C1-C18 alkyl or halogen-substituted C1-C18 alkyl.

6. The electron transport material according to any one of claims 1 to 5, characterized in that n=2~32; Optionally, n is a multiple of 2; Optionally, n is 2-16.

7. The electron transport material according to any one of claims 1 to 6, characterized in that The HOMO energy level of the electron transport material is -7.14eV to -6.47eV, and the LUMO energy level is -3.83eV to -3.32eV.

8. The method for preparing an electron transport material according to any one of claims 1 to 7, characterized in that: The steps include: Conducting a free radical polymerization reaction between compound 1 and compound 2; Among them, the structural formula of compound 1 is The structural formula of compound 2 is A0, B1, B2 have the same meanings as in claim 1, and n1+n2=n.

9. The method for preparing an electron transport material according to claim 8, characterized in that: The conditions of the free radical polymerization reaction include: reacting in the presence of a halogenating agent and under light conditions; Optionally, the halogenating agent is N-bromosuccinimide; Optionally, the solvent used in the reaction includes an alkane solvent; Optionally, the reaction time is 2 min to 10 min; Optionally, the illumination is performed using a mercury lamp, and the power of the mercury lamp is 400W to 600W.

10. The method for preparing an electron transport material according to any one of claims 8 to 9, characterized in that: The preparation steps of compound 1 include: Substituting compound 1-1 with compound 1-2; Among them, the structural formula of compound 1-1 is B1-B(OH)2, and the structural formula of compound 1-2 is X2 is halogen.

11. The method for preparing an electron transport material according to any one of claims 8 to 10, characterized in that: The preparation steps of compound 3 include: Substitution reaction of compound 3-1 with compound 3-2; Among them, the structural formula of compound 3-1 is B2-B(OH)2, and the structural formula of compound 3-2 is X3 is halogen.

12. The method for preparing an electron transport material according to any one of claims 10 to 11, characterized in that: The conditions of the substitution reaction include: conducting the reaction in the presence of a catalyst; Optionally, the catalyst comprises tetrakis(triphenyl)phosphine palladium; Optionally, the reaction temperature is heated to reflux, and the reaction time is 10h to 30h; Optionally, the solvent used in the reaction includes one or both of tetrahydrofuran and water.

13. A perovskite solar cell, characterized in that: It comprises a transparent electrode and a functional layer and an electrode layer sequentially stacked on the transparent electrode, wherein the functional layer comprises an electron transport layer, a hole transport layer, and a perovskite layer arranged between the electron transport layer and the hole transport layer; the material of the electron transport layer comprises the electron transport material according to any one of claims 1 to 7.

14. The perovskite solar cell according to claim 13, characterized in that: The hole transport layer is closer to the transparent electrode than the electron transport layer.

15. The perovskite solar cell according to claim 13 or 14, characterized in that: The general structural formula of the material of the perovskite layer is ABX3 or A2CDX6, wherein A is a monovalent cation, B is a divalent metal cation, C and D are a monovalent metal cation and a trivalent metal cation, respectively, and X is a monovalent anion; Optionally, A includes organic cations, Li + 、Na + , K + , Rb + and Cs + One or more of; Optionally, the organic cation includes methylamine (MA + ), ethylamino, propylamino, butylamino, pentylamino, hexylamino, formamidinium (FA + ) and at least one of an imidazole group; Optionally, the A comprises an organic amine ion and a Cs + One or more of; Optionally, the B includes Pb 2+ Sn 2+ 、Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ 、Zn 2+ ,Ge 2+ , Fe 2+ , Mn 2+ 、Co 2+ , Sb 2+ , Cu 2+ and Ni 2+ One or more of; Optionally, B includes Pb 2+ and Sn 2+ One or both of the following: Optionally, the C includes Ag + , Cs + , K + And Ru + One or more of; Optionally, the D includes Bi 3+ 、N i3+ , Fe 3+ , Cu 3+ , Sb 3+ andIn 3+ One or more of; Optionally, the X includes I - Br - and Cl - One or more of .

16. An electrical device, characterized in that: A perovskite solar cell comprising the method according to any one of claims 13 to 15.